INCREASING EDUCATIONAL AWARENESS OF PARENTING STYLES AND FAMILY SOCIAL SUPPORT ON ADOLESCENT MENTAL HEALTH - Juwinner Dedy Kasingku; Winda Novita Warouw; Edwin Melky Lumingkewas (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
Good mental health requires the ability to manage emotions, thoughts, and actions in a healthy and adaptive manner. Parental upbringing and family support are crucial in maintaining the mental health of adolescents, as they are the closest individuals within the family. Emotional support from the family and access to mental health resources like psychologists or mental health clinics can assist adolescents in overcoming stress and pressures in their lives. This paper uses a literature review methodology to explore the family’s role in adolescent mental health. The findings based on the literature review indicate that the family has a significant influence on adolescent mental health. Parenting styles demonstrated by parents have a significant impact on the mental development of adolescents. The social support provided by parents to their children is likewise crucial. With strong social support from the family and the surrounding environment, adolescents can build positive relationships with others, effectively overcome challenges, and achieve desired life goals.